Myopia Control Efficacy of Spectacle Lenses with Dual-Index Aspherical Lenslets: A 1-Year Randomized Clinical Trial - Yee Ling Wong, PhD; Andrew Tan, BBus; Ee Woon Lim; Hua Ren Chua; Liang Shen, PhD; Matthieu Guillot, MSc; Björn Drobe, PhD (Ophthalmology Science)
Objective: To examine the myopia control efficacy, in terms of axial elongation, of a new myopia control spectacle lenses with Dual-Index Aspherical Lenslets (DIAL) embedded within the lens, compared with single-vision spectacle lenses (SVLs) over a 1-year period. Design: A prospective, randomized, double-masked clinical trial. Participants: Eighty children aged 8 to 13 years with myopia (spherical equivalent refraction [SER] between −0.75 and −4.75 diopters [D]) were recruited. Intervention: Participants were randomized to either the DIAL or SVL spectacle lenses group (1:1 ratio). Main Outcome Measures: Axial length (AL), noncycloplegic subjective refraction, and best-corrected visual acuity (BCVA) were measured at baseline and 6-month intervals. Questionnaires on adaptation and compliance were administered during all visits. Results: A total of 76 (N = 38 in each group) participants (mean [standard deviation] age, 10.8 [1.6] years) completed the 1-year visit. Mean (± standard error) 1-year AL change in the DIAL and SVL groups was 0.04 ± 0.02 and 0.22 ± 0.04 mm, respectively. A mean difference of −0.18 mm (95% confidence interval [CI], −0.26 to −0.10 mm; P < 0.001) was found. Mean 1-year SER change in the DIAL and SVL groups was −0.13 ± 0.06 and −0.39 ± 0.08 D, respectively, with a mean difference of 0.26 D (95% CI, 0.06–0.46 D; P = 0.01). Compared with SVL, younger children (8 to <11 years) and older children (11–13 years) in the DIAL group had significantly less axial elongation (−0.29 mm less for younger children and −0.09 mm less for older children), with greater myopia control effect of DIAL spectacle lenses among the younger group than among the older group (P = 0.004 for interaction). No significant differences between the lens groups were found for distance BCVA (P = 0.36). All participants adapted within 3 to 4 days regardless of lens group. No significant differences in mean daily wearing time were seen between the DIAL and SVL groups (P = 0.53). Conclusions: Dual-Index Aspherical Lenslets spectacle lenses showed good myopia control efficacy, in terms of axial elongation, compared with SVL, among children aged 8 to 13 years in Singapore. Financial Disclosure(s): Proprietary or commercial disclosures may be found in the Footnotes and Disclosures at the end of this article.